Chelate-assisted phytoextraction using Brassicaceae plants - Walid Saibi; Faical Brini (Open Journal of Environmental Biology - Peertechz Publications, 2020)
In these last decades, excessive metal concentration pose serious contamination in soils. Therefore, it is urgent to develop and adopt a new strategy and technology to remove soil contaminants. Here, the phytoextraction was considered as a recently developed approach to clean up metal-polluted soils in that the plants are used to translocate the toxic metals from the contaminated soils. Therefore, this mini-review provides a perfection of recent knowledge related to the heavy metal phytoextraction from soils and their accumulation in plants. It has been reported that EDTA enhances the availability of heavy metal to plants and thus increases the accumulation in their shoots. In addition, fundamental and basic advancement has been made on the molecular aspects and the physiological regarding tolerance and metals phytoaccumulation in plants. A multidisciplinary strategy is warranted to make phytoextraction a plausible trade technology to remediate metal-polluted soils. Hence, the purpose is to integrate soil-related and biological progress to suggest research needs and future direction.